"Miguel es un artista"—and Luisa is an excellent student: Seeking time and space for children's multimodal practices. (September 2014) - Falchi, Lorraine T; Axelrod, Ysaaca; Genishi, Celia
This paper draws data from a 5-year ethnographic study of young multilingual (Mixteco/Spanish/English) children in their early childhood classrooms. In this paper, we focus on two of the children and their distinctive paths as they develop language and literacy. Using a sociocultural and multimodal theoretical framework we examine how these two children participate in and negotiate a balanced literacy curriculum.